A Dangerous Dream in (Re)building the Hungarian Nation - Hanga András (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. A museum as a scientific and informative institution should have numberless motives so that it is not only a shallow foundation: collection, categorization, restoration, knowledge-transmission, remembrance, research, emotion and intentionless analysis, publicity, conferences, publications, explanatory texts, multilingual tags, museum pedagogy, etc. Can the Trianon Museum be considered as a museum or is it something else? Exhibition, place of pilgrimage, shrine? Is it the field of a posttraumatic self-therapy? Or the tool of historicizing a nation's (re)building? Or is it a mixture of the above? Why was it only presented in the radical angled media organs and hardly ever appeared in the mainstream media? In this work we make an attempt – in the light of the evolving political intention – to give multiple answers to the questions raised by the reception of the Trianon-discourse which is shown in the museum.

Egy múzeumnak, mint tudományos és tudományos ismeretterjesztő intézménynek számos dologgal kell rendelkeznie, hogy ne csak a megnevezésében legyen múzeum: gyűjtés, kategorizálás, restaurálás, tudásközvetítés, emlékezés, kutatás, érzelem és intenciómentes elemzés, nyilvánosság, publikálás, konferenciák, kiadványok, értelmező szövegek, többnyelvű feliratok, múzeumpedagógia és így tovább. Vajon a Trianon Múzeum tekinthető-e egyáltalán múzeumnak, vagy az valami más? Zarándokhely, kegyhely, kiállítás? Netán poszttraumás önterápia helyszíne? Talán a historizáló nemzet(újjá)építés eszköze? Vagy a fentiek keveréke? Médiamegjelenését vizsgálva felvetődik a kérdés, hogy miért csak a radikális beállítottságú lapokban jelent meg, a mainstream médiában alig? Az elemzésben kísérletet teszek arra – a kibontakozó politikai szándék fényében –, hogy a múzeumban láthatóvá tett Trianondiskurzus recepciója által a fent felvetett kérdésekre értelmezéssel választ adjak.

Резюме. Музей як наукова і науково-популярна установа повинен діяти у різних сферах, аби бути музейною установою не тільки у назві: збір, категоризація, реставрація, поширення наукових знань, згадування, дослідження, беземоційний та безпристрасний аналіз, публічність, публікації, конференції, видання, тлумачення текстів, багатомовні написи, музейна педагогіка і так далі. Цікаво, чи можна Тріанонський музей вважати музеєм чи це щось інше? Місце прощі, святиня чи виставка? Можливо місце посттравматичної самотерапії? А може засіб історичної (від)будови нації? Чи можливо це суміш усього перерахованого? Якщо проаналізувати відгуки у ЗМІ, то постає питання: чому інформація з’явилася тільки у пресі радикального спрямування, а в популярних видання – ні? У статті зроблено спробу – у світлі сучасних політичних намірів – дати відповідь на озвучені питання крізь призму рецепції представленого в музеї дискурсу Тріанону.
A magyar nemzet(újjá)építés kényes ábrándja
Делікатна мрія (від)будови угорської нації
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008907
Keywords: Competitive identity and remembrance politics; Trianon; museum; Trianon-discourse